Supramolecular Assembly of Shape Memory and Actuating Hydrogels for Programmable Shape Transformation - Zhuo, Jie; Wu, Baoyi; Zhang, Jiawei; Peng, Yu; Lu, Huanhuan; Le, Xiaoxia; Wei, Shuxin; Chen, Tao (ACS applied materials & interfaces, 2022)
The deformable diversity of organisms in nature has inspired the development of bionic hydrogel actuators. However, the anisotropic structures of hydrogel actuators cannot be altered after the fabrication process, which restricts hydrogel actuators to provide complex and diverse shape deformations. Herein, we propose a dual programming method to generate numerous anisotropic structures from initial isotropic gelatin-containing hydrogels; the isotropic hydrogel blocks could be first assembled into anisotropic structures based on the coil-triple helix transition of gelatin, and then, the assembled hydrogels could further be fixed into various temporary anisotropies, so that they can produce complex and diverse deformations under the stimulation of pH. In addition, the shape programming and deformation behaviors are reversible. This dual programming method provides more potential for the application of hydrogel actuators in soft robots and bionics.